Rho Kinase Inhibition Rescues the Endothelial Cell Cerebral Cavernous Malformation Phenotype - Borikova, Asya L. (American Society for Biochemistry and Molecular Biology, 2010)
Cerebral cavernous malformations (CCM) are vascular lesions causing seizures and stroke. Mutations causing inactivation of one of three genes, ccm1, -2, or -3, are sufficient to induce vascular endothelial cell defects resulting in CCM. Herein, we show that loss of expression of the CCM1, -2, or -3 proteins causes a marked increase in expression of the GTPase RhoA. Live cell imaging with a RhoA-specific biosensor demonstrates increased RhoA activity with loss of CCM1, -2, or -3, with an especially pronounced RhoA activation in both the cytosol and the nucleus with loss of CCM1 expression. Increased RhoA activation was associated with Rho kinase-dependent phosphorylation of myosin light chain 2. Functionally, loss of CCM1, -2, or -3 inhibited endothelial cell vessel-like tube formation and extracellular matrix invasion, each of which is rescued by chemical inhibition or short hairpin RNA knockdown of Rho kinase. The findings, for the first time, define a signaling network for CCM1, -2, and -3 in CCM pathology, whereby loss of CCM1, -2, or -3 protein expression results in increased RhoA activity, with the activation of Rho kinase responsible for endothelial cell dysregulation. The results define Rho kinase as a therapeutic target to rescue endothelial cells from loss of CCM protein function.